2020
DOI: 10.21203/rs.3.rs-35639/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors and Maternal-Fetal Outcomes of Pregnant with Preeclampsia Who Converted to Cesarean Section After A Trial Vaginal Birth

Abstract: Background: At present, most pregnant with preeclampsia choose direct cesarean section. Whether cesarean section after vaginal trial affects the outcome of mother and child and its related risk factorsIt are still unclear. The purpose of this study is to investigate the risk factors and maternal-neonatal outcomes in severe preeclampsia patients who undergo transfer-cesarean section during vaginal labor. Methods: For this retrospective study, patient with severe preeclampsia data from 2015 to 2019 was collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…Our study showed that a higher proportion of women with preeclampsia had a cesarean section. This was expected and similar to what other studies on severe preeclampsia and hypertensive disorders have found [19,20]. In both women with gestational hypertension and women with preeclampsia in this study, around 12% of the newborn had low birth weight (<2500 g).…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that a higher proportion of women with preeclampsia had a cesarean section. This was expected and similar to what other studies on severe preeclampsia and hypertensive disorders have found [19,20]. In both women with gestational hypertension and women with preeclampsia in this study, around 12% of the newborn had low birth weight (<2500 g).…”
Section: Plos Onesupporting
confidence: 92%
“…Many patients and obstetricians prefer cesarean section over vaginal delivery because cesarean section expedites delivery which might reduce the risk of morbidity and perinatal death [23]. However, studies have supported and recommended vaginal delivery in preeclampsia if there is no other indication of cesarean section [19,24]; even so health professionals fear that vaginal delivery will worsen the maternal and fetal condition [19,23]. Further, our study was not able to categorize preeclampsia with or without severe features; as preeclampsia with severe features might lead to more cesarean deliveries [6].…”
Section: Plos Onementioning
confidence: 99%